Synthesis of Bulk Kesterite – A Prospective Photovoltaic Material. Issue 28 (8th September 2014) - Podsiadlo, Slawomir; Bialoglowski, Maciej; Matyszczak, Grzegorz; Marek, Paulina; Gebicki, Wojciech; Bacewicz, Rajmund; Stachowicz, Marcin; Dluzewski, Piotr; Wozniak, Krzysztof
Abstract: A rapid development of photovoltaics has been observed recently. Permanent interest in new cheap and efficient photovoltaic devices stimulates a constant search for new semiconductor materials and structures. The success of materials based on CIGS (CuIn1– x Ga x Se2 ) is limited by the prohibitive prices of the elements In and Ga. A family of quaternary semiconducting materials of the Cu2 ZnSnS4 type, crystallizing mainly in the kesterite structure, offers a promise of new cheap photovoltaic materials. Kesterite is manufactured from nontoxic and naturally abundant materials. The energy gap of Cu2 ZnSnS4 is about 1.5 eV, and the absorption coefficient of this direct‐band‐gap material is α > 10 4 cm –1 for photon energies higher than the energy gap. In this paper, we report a method of obtaining free‐standing single crystals of kesterite (Cu2 ZnSnS4 ). Abstract : An advanced synthesis and characterization of bulk single crystals of kesterite are reported. Mixtures of powders of CuS, ZnS, and SnS2 were annealed in vacuo in quartz ampoules at 500–1100 °C to obtain free‐standing single crystals of kesterite. SEM, TEM, XRD, Raman, and EXAFS measurements confirm the excellent structural properties of Cu2 ZnSnS4 bulk single crystals.